Tb927.10.6900 encodes the glucosyltransferase involved in synthesis of base J in Trypanosoma brucei - Sekar, Aarthi (2014)
Base J is a DNA modification found in the genome of Trypanosoma brucei and all other kinetoplastids analyzed, where it replaces a small fraction of Ts, mainly in telomeric and chromosome-internal transcription initiation and termination regions. The synthesis of base J is a two-step process whereby a specific T is converted to HOMedU (hydroxymethyldeoxyuridine) and subsequently glucosylated to generate J. The thymidine hydroxylases (JPB1 and JBP2) that catalyze the first step have been characterized, but the identity of the glucosyltransferase catalyzing the second step has proven elusive. Recent bioinformatic analysis by Iyer et al. [Nucleic Acids Res. 2013; 41, 7635] suggested that Tb927.10.6900 encodes the glucosyltransferase (HmdUGT) responsible for converting HOMedU to J in T. brucei. We now present experimental evidence to validate this hypothesis; null mutants of Tb927.10.6900 are unable to synthesize base J. Orthologues from related kinetoplastids show only modest conservation, with several insertion sequences found in those from Leishmania and related genera.